Adverse effects of atmospheric pollution on public health in Brazil: an integrative review (SciELO Preprints, 2024)
Introduction: Atmospheric contamination is closely linked to negative impacts on public health. Understanding the unique aspects of the Brazilian context is crucial for the implementation of public policies and health promotion. Objective: To assess the negative impacts of air pollution on public health in Brazil. Method: This review was developed through a search in the Latin American and Caribbean Health Sciences Information Literature (LILACS), Scientific Electronic Library Online (SciELO), and PubMed/Medline databases, using the keywords “Air Pollution” AND (Health OR “Public Health”) AND “Adverse Effects” AND Brazil. Articles written in English and Portuguese, published from 2013 to 2024, were selected. Additionally, two articles were manually included. After applying the inclusion criteria and removing duplicates, 19 references were used for this review. Results and Discussion: There is a significant correlation between respiratory diseases and the emission of atmospheric pollutants, particularly the release of fine suspended particles (PM10), highlighting an increase in hospitalizations due to respiratory illnesses. The lack of studies addressing the effects of pollutants on other systems of the human body beyond the respiratory and cardiovascular systems, as well as the scarcity of information on various atmospheric pollutants, underscores the need for further research to fill these gaps. Conclusion: Even at levels considered acceptable, atmospheric pollutants still pose risks to public health. Therefore, specific public policies aimed at reducing emissions of these gasses and improving air quality are necessary.